Solving the cryptic diversity of the genus Manerebia Staudinger in northern Peru: description of new species and considerations on the biogeographical role of the Huancabamba Deflection (Nymphalidae: Satyrinae: Pronophilina) - Mahecha-J., Oscar; Florczyk, Klaudia; Willmott, Keith; Cerdeña, José; Zubek, Anna; Boyer, Pierre; Farfán, Jackie; Lachowska-Cierlik, Dorota; Pyrcz, Tomasz W. (Zootaxa, 2021)
The Huancabamba Deflection in the Andes of northern Peru and southern Ecuador is a pivotal area for Neotropical biogeography, where exceptional biodiversity coincides with high rates of endemism. These characteristics are well illustrated within the montane butterfly genus Manerebia Staudinger (Nymphalidae, Satyrinae). Here, six new, apparently endemic species, and two new subspecies, are described from this region: M. inducta Pyrcz & Willmott n. sp., M. ronda Pyrcz & Boyer, n. sp., M. ronda amplia Pyrcz & Boyer, n. ssp., M. punku Pyrcz & Farfán n. sp., M. huamanii Cerdeña & Pyrcz n. sp., M. placida Pyrcz & Willmott n. sp., M. granatus Willmott, Radford & Pyrcz n. sp. and M. prattorum udima Pyrcz & Boyer, n. ssp. A total of 22 species of Manerebia is reported from the study region, as much as half the total number of species in this genus distributed throughout the tropical Andes. The alpha-taxonomy of Manerebia is particularly demanding, as colour patterns have apparently converged among different species making identification virtually impossible in some cases without comparison of their genitalia, which prove taxonomically and phylogenetically highly valuable. On the other hand, several species differ markedly in wing colour patterns and occur at different elevations but have identical genitalia. Furthermore, our data show that DNA barcoding is only partly viable as an alpha-taxonomic tool, as some markedly different species of Manerebia, in terms of external morphology and ecological preferences, are genetically not separable using only COI markers. On the other hand, several species barely differing morphologically are identified based on barcode. Barcodes of 26 species, including 18 from the northern Andes, are studied here, showing strong differences within some taxa previously considered conspecific based on morphological characters, suggesting that their taxonomic status needs to be re-evaluated. In particular, M. trimaculata and the widely distributed polytypic M. inderena may be highly variable species or complexes of several species. A total of 16 species are found north of the Chamaya valley in southern Ecuador and extreme northern Peru, compared to 14 species south of it in northern Peru. The faunal (Jaccard) similarity coefficient of the two adjacent regions is low (0.3), reflecting the role of the Huancabamba Deflection as a biogeographical barrier.